The effects of acceptance and commitment therapy on psychosocial impact and adherence of MDR-TB patients - Priyo Purnomo As'hab; Budi Anna Keliat; Ice Yulia Wardani (SAGE Publishing, 2021)
Background: The Worldwide resistance prevalence of the first-line TB drug, rifampicin (RR-TB), in 2017 was 7.4 per 100,000 population, and 82% of them experienced multidrug-resistant tuberculosis (MDR-TB). Indonesia is the top 20 country with an MDR-TB burden, and its prevalence is 8.8 per 100,000 population. MDR-TB requires a long-time treatment and has accompanying side effects: biological and psychosocial effects. However, efforts to overcome the psychosocial impacts have not been conducted. This study aims to determine the effect of acceptance and commitment therapy (ACT) on anxiety, depression, suicidal ideation, and treatment adherence in MDR-TB patients. Design and methods: This research employed a quasi-experimental design with a pre-test three post-tests using total sampling. The pre-test was conducted before the standard nursing intervention, post-test 1 was after the standard nursing intervention, post-test 2 was after ACT session 1, and post-test 3 was after ACT session 2. Data were collected by the Hamilton Rating Scale for Anxiety (HAM-A), Beck Hopelessness Scale (BHS), a Scale for Suicide Ideation (SSI), and Morisky Medication Adherence Scale (MMAS). Results: The standard nursing action and ACT reduce anxiety (p = 0.002), reduced depression (p = 0.0001), reduced suicidal ideation (p = 0.008), and increased treatment adherence (p = 0.0001). Conclusions: The standard nursing action and ACT reduce anxiety, depression, and suicidal ideation. They increase treatment adherence recommended for use in MDR-TB patients.